Climatic Parameters and Rotavirus Diarrhea Among Hospitalized Children: A Study of Eastern India - Ghoshal, Vishwanath; Das, Rashmi Ranjan; Nayak, Manas Kumar; Singh, Snigdha; Das, Palash; Mohakud, Nirmal Kumar (Frontiers in Pediatrics, 2020)
Background: Rotavirus diarrhea is often referred to as "Winter Diarrheal Disease" as it causes nearly 50% of the pediatric hospitalizations during the winter season. This study was done with the objective of bringing out the epidemiological nexus of rotavirus cases with different seasonal parameters like maximum, minimum temperature, humidity, and average rainfall. Methods: This prospective observational study was conducted in a tertiary care teaching hospital in Eastern India from February 2016 to December 2018. Data on daily maximum and minimum temperature, relative humidity, and rainfall were collected. Result: Of 964 children admitted, 768 stool samples were collected for rotavirus assay. A total of 222 children (23%) were positive. The maximum, minimum temperature, average rainfall, and average humidity of 83.4 mm, 79.2%, 28.1, and 21.9, respectively were significantly associated with positive rotaviral cases. Conclusion: There is a positive association between maximum, minimum temperature, average rainfall, and average humidity with a percentage prevalence of rotaviral cases. The knowledge about the seasonal pattern in a particular geographical area would help the reallocation of hospital services (staff and bed) to tackle the epidemic or emergency situations resulting from the clustering of cases.